Effect of sowing methods on different varieties of rapeseed under rainfed condition - Bhandari, Sagar (2024)
The most crucial variables affecting the yield of rapeseed are the sowing method and varieties, each of which is influenced by the production system, farmers’ knowledge, and the innovative use of technologies. The aim of this study is to determine how rapeseed production potential is affected by sowing technique and variety. Three varieties (Pragati, Unnati, and Chitwan-Local) and two planting techniques (Broadcasting and Line Sowing) were used in the field trial in Fulbari, Dang, during the winter of 2021, with four replications. The experimental design used was Randomized Complete Block Design. Differences between the varieties, sowing techniques, and their interaction on eventual seed production were found to be statistically highly significant. The yield of rapeseed was highest when Chitwan Local was line sown (2.17 t.ha-1) and lowest when Pragati was broadcasted (1.56 t.ha-1). Statistically significant effect was found on mean values of seed yield when seed were line sown rather than broadcasted i.e. 1.85 t.ha-1 compared to 1.71 t.ha-1 respectively. Among the varieties the economical yield was found to be maximum in Chitwan Local (1.88 t.ha-1) followed by Unnati (1.81 t.ha-1) whereas lowest in Pragati (1.65 t.ha-1). Line sowing of Chitwan Local variety produces better outcomes under rainfed condition. For better rapeseed yield performance under a rainfed condition, this study will be helpful in the selection of varieties and sowing techniques.